Comparison of In-Office Dental Bleaching with 25% Hydrogen Peroxide Using or not Activation with Zoom® Halogen Light Lamp - Posso Moreno, Sandra Lorena; Pontificia Universidad Javeriana (Editorial Pontificia Universidad Javeriana, 2010)
Background: Tooth whitening is one of the mostly used treatments to improve dental esthetics. Dental bleaching techniques include the use of substances such as carbamide peroxide, sodium perborate, and hydrogen peroxide. Researchers and clinicians are often seeking to know which techniques produce the best results. Purpose: To determine whether the use of halogen light with 25% hydrogen peroxide in in-office tooth bleaching is more effective than the use of hydrogen peroxide alone. Methods: A controlled clinical trial was carried out. Upper maxilla of 10 healthy patients received whitening therapy with 25% hydrogen peroxide. Using the divided maxilla method, one quadrant of each patient was exposed to halogen light for 20 minutes and the other did not. The in-office procedure was carried out in two sessions of 20 minutes each. Color in each quadrant was measured before and after the therapy with the Vita EasyShade color guide. Results: The use of halogen light with tooth bleaching with 25% hydrogen peroxide did not show statistically significant differences with the use of hydrogen peroxide alone regarding color change (p=0,38).